Staging Affectivity through Expressive Dance Movement: The 60+ Community Dance Program at Copenhagen's Dansekapellet. Issue 3 (3rd July 2021) - Conrad, Robin
ABSTRACT: This case study focuses on the lived experiences of participants in a Danish community dance program for dancers over sixty years of age and centers on how dance in this setting contributes to building affectivity; that is, what motivates participants' movement and moves them. Participants describe their affective experiences as developing through dancing in three main ways, by attending to: 1) the spatiality of their own bodies and the space itself, 2) the qualities with which they move, and 3) their own kinesthetic awareness. Additional elements contribute to participants' affective experience, such as the instructors' approaches and their metaphoric verbal cuing. By considering the material and interpersonal components that shape an affective experience as a lens to understand the data, this article aims to detail how phenomenological aspects of affectivity unfold and are productive in this particular community dance setting.